Development of a citrus peel-based biorefinery strategy for the production of succinic acid - Patsalou, Maria; Menikea, Kristia Karolina; Makri, Eftychia; Vasquez Christodoulou, Marlen; Drouza, Chryssoula; Koutinas, Michalis (My University, 2017)
A preliminary study has been performed for the valorization of citrus peel waste (CPW) through the biorefinery platform aiming to produce succinic acid. Following extraction of essential oils and pectin, different conditions of dilute acid hydrolysis were evaluated based on estimation of the sugars liberated and subsequent fermentation of hydrolyzates for production of succinic acid by Actinobacillus succinogenes. The most suitable pretreatment conditions involved 116 degrees C for 10 min using 5% (w/v) of dry raw material (drm). Thus, a total sugar (ts) yield of 0.21 g(ts) g(drm)(-1) and a succinic acid (sa) yield via microbial fermentations of 0.77 g(sa) g(tsc)(-1) was achieved, while the use of lower solid contents resulted in higher sugar yields. The residues from dilute acid hydrolysis were applied for subsequent enzyme hydrolysis using commercial enzymes and the most suitable combination of enzyme units included 30 IU cellulases and 25 BGL beta-glucosidases achieving a yield of 0.58 g(ts) g(drm)(-1). Moreover, elemental analysis in hydrolyzates obtained from dilute acid hydrolysis and a combination of acid and enzyme hydrolysis indicated that during the combined treatment, high concentrations of Mg2+ and Ca2+ ions are liberated as compared to dilute acid hydrolysis, while the concentration of hydroxymethylfurfural was 0.038 g L-1 demonstrating low formation of inhibitors. The hydrolyzate generated through the combined pretreatment proposed was applied as feedstock for the production of succinic acid achieving a yield of 0.70 g(sa) g(tsc)(-1). However, although the combined hydrolysis approach could approximately double the sugars released in the hydrolyzate, the economic analysis performed confirmed that the use of the enzymatic treatment could not be competitive. The developed bioprocess constitutes a valuable alternative to the application of energy intensive chemical technologies for succinic acid production.
Keywords: Citrus peel waste; Actinobacillus succinogenes; Succinic acid; Biorefinery; Bioprocess